Aplikasi Pemesanan Jasa Undangan Pernikahan Berbasis AR (Augmented Reality) Menggunakan Metode Design Thinking - Muhammad Iqbal Wicaksono; Eva Yumami; Niky Hardinata (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
A wedding is an important event in a person's life that requires various careful preparations, one of which is sending invitations to guests. This research aims to create an Android-based wedding invitation booking application that utilizes Augmented Reality (AR) technology with a Design Thinking approach. This approach includes five main stages, namely empathize, define, ideate, prototype, and testing, to ensure that the developed application is truly in accordance with the needs and expectations of users. With AR technology, users can view and interact directly with virtual invitations through digital devices such as smartphones, which provides a more engaging, interactive, and modern visual experience than conventional physical invitations. The app's key features include invitation design selection, content customization (name, location, date, and couple's photo), as well as simulated invitation display with three-dimensional effects via AR. The app also allows users to store, share, and place orders directly through an integrated system. The results of the evaluation conducted using the System Usability Scale (SUS) method showed a score of 75.3. This score indicates that the app has a good usability level and is positively received by the majority of respondents. In addition, this application is considered to be able to increase efficiency in the invitation ordering process and provide a more modern and personal impression to users and invited guests. The conclusion of this study is that AR-based wedding invitation booking apps not only serve as a practical tool, but also become digital innovations that enrich the user experience in modern weddings. This research is expected to make a real contribution to the development of creative information technology and inspire other developers to create similar solutions that are innovative, efficient, and relevant to the needs of the times.